SINTESA PERAN DSS (SISTEM PENDUKUNG KEPUTUSAN) DALAM MANAJEMEN DAN PERKEMBANGANANNYA DI PERUSAHAAN - Indriyanti, Aris (PRIMA EKONOMIKA, 2024)
DSS impacts decision making in a company, using a focus on planning and the use of strategic tools. DSS has a large and diverse impact on a company's development. Strategy formulation requires an accurate picture of the competitive environment to adapt quickly and to secure new opportunities (Ofori & Atiogbe 2012). In corporate strategy and operations, resulting in product changes, the implementation of new and more dynamic DSS systems can lead to a rethinking of the strategic tools used by senior management and the definition of new long-term strategic objectives. In conclusion, the cultural predisposition to adopt DSS has a determining influence during strategic planning and operations; because the strategy for DSS has to be more than just implementing technological changes it actually has to be in place before the adoption of new technology is considered demanding commitment from the senior management team as well as the operational side of the Company Keywords: DSS, Management, Technological development